2004
DOI: 10.1017/s0022112004009425
|View full text |Cite
|
Sign up to set email alerts
|

Gravity-driven flow of continuous thin liquid films on non-porous substrates with topography

Abstract: Article:Gaskell, P.H., Jimack, P.K., Sellier, M. et A range of two-and three-dimensional problems is explored featuring the gravitydriven flow of a continuous thin liquid film over a non-porous inclined flat surface containing well-defined topography. These are analysed principally within the framework of the lubrication approximation, where accurate numerical solution of the governing nonlinear equations is achieved using an efficient multigrid solver.Results for flow over one-dimensional steep-sided topogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
134
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(143 citation statements)
references
References 33 publications
9
134
0
Order By: Relevance
“…While the generality of these results may be restricted somewhat by the limitations of the lubrication analysis, it has previously been shown that the results of lubrication theory are in good agreement with boundary integral computations of the unsimplified Stokes equations for the flow of an isothermal film over topography for small capillary numbers ͑CaϽ 0.01͒, even for very steep topographical features. 42 Finite element solutions 43 of the full Navier-Stokes equations further confirm the accuracy of the lubrication solutions in this regime even though some of the restrictions inherent to the reduction in dimensionality of lubrication theory are not entirely satisfied. The results presented here are therefore expected to be valid for such small capillary numbers that correspond to thin films.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…While the generality of these results may be restricted somewhat by the limitations of the lubrication analysis, it has previously been shown that the results of lubrication theory are in good agreement with boundary integral computations of the unsimplified Stokes equations for the flow of an isothermal film over topography for small capillary numbers ͑CaϽ 0.01͒, even for very steep topographical features. 42 Finite element solutions 43 of the full Navier-Stokes equations further confirm the accuracy of the lubrication solutions in this regime even though some of the restrictions inherent to the reduction in dimensionality of lubrication theory are not entirely satisfied. The results presented here are therefore expected to be valid for such small capillary numbers that correspond to thin films.…”
Section: Discussionmentioning
confidence: 86%
“…Lubrication theory was found to be accurate within this regime even for very steep features, as the slope of the free surface, and not that of the topographical feature, is the relevant constraint. 42 Comparisons to finite element solutions 43 of the full Navier-Stokes equations and to experiments 44 further confirm that lubrication theory provides surprisingly accurate results even when it is applied to situations in which its inherent restrictions are seemingly violated.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Topographies are defined via arctangent functions which enable the steepness of their sides to be controlled easily and the boundary conditions are that the flow is fully developed upstream and downstream. Further details are given in [4].…”
Section: Problem Specification and Mathematical Formulationmentioning
confidence: 99%
“…Recently, however, a Multigrid approach with adaptive time-stepping has been developed as a more efficient alternative to ADI schemes, having already been applied successfully to droplet spreading flows [3] and continuous film flow with [4] or without evaporation [5]. This paper highlights the additional benefits of adopting an automatic local grid refinement procedure within the Multigrid algorithm which allows fine grids to be used only where they are needed, i.e.…”
Section: Introductionmentioning
confidence: 99%